RESEARCH TRADITIONS OF PHYSICAL EDUCATION OF YOUTH KARACHAIS - Kazim Ortabaev (Вестник Северо-Кавказского федерального университета, 2022)
The article attempts to review some aspects of the traditional culture of physical education of young people in one of the indigenous ethnic groups of the North Caucasus - Karachai. The article shows the features ofphysical education Karachay due to the economic way of life and way of life.